2020
DOI: 10.2147/cmar.s248374
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of Risk Factors for Lymph Node Metastases in Elderly Patients with Papillary Thyroid Micro-Carcinoma</p>

Abstract: Background: With guidance from the American Joint Committee on Cancer (AJCC) Cancer Staging Manual, 8th edition, we explored the characteristics of central lymph node metastasis (CLNM) of papillary thyroid micro-carcinoma (PTMC) in elderly patients ≥55 years of age. Our goal was to provide references for establishing a lymph node dissection scheme in such patients. Methods: We retrospectively analyzed the clinical data of thyroid cancer patients admitted to the Head and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…In this study, age was an important predictive factor, especially in patients below 45 years. Previous studies have determined age (< 45 years) as an independent risk factor [ 34 , 36 ], and we found similar results in this study. Jiwang et al [ 8 ] found that CLNM within PTMC patients was higher among males and younger individuals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, age was an important predictive factor, especially in patients below 45 years. Previous studies have determined age (< 45 years) as an independent risk factor [ 34 , 36 ], and we found similar results in this study. Jiwang et al [ 8 ] found that CLNM within PTMC patients was higher among males and younger individuals.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, age (< 45 years), sex, tumor size, multifocality, capsular invasion, and HT to be the risk factors that independently predicted CLNM among PTMC cases, which was similar to the risk factors determined in previous studies [ 8 , 34 36 ]. However, the significant CLNM predictive risk factors among PTMC were dissimilar partially.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data demonstrate that up to 51% of patients with T1-T2, non-invasive, cN0 PTC harbored central lymph node metastases. Such a high incidence of regional lymph node involvement is similar to other findings (18)(19)(20) and indicates that thyroid cancer is predisposed to LNM and that preoperative ultrasound currently fails to detect a massive number of patients with clinically significant lymph nodal disease (21,22). Therefore, an accurate diagnosis of lymph node status carries much weight in helping clinicians determine the precise treatment for patients as well as informing the patients of prognoses and we advocate a selective approach to pCLND, particularly for cases with a high risk of CLNM.…”
Section: Discussionsupporting
confidence: 91%
“…Most patients have a good prognosis, especially PTMC patients, whose cancer-related mortality rate is merely 0.34% after treatment ( 11 , 12 ). Whereas PTMC patients have a high CLNM rate, studies have pointed out that 28% of PTMC patients are diagnosed with CLNM ( 13 , 14 ). Thyroid cancer diagnosis and treatment guidelines (2022) published by the National Health Commission of the People’s Republic of China recommended prophylactic CLND should be performed for PTC patients as long as the parathyroid gland and recurrent laryngeal nerve can be protected ( 15 ).…”
Section: Discussionmentioning
confidence: 99%